Methods to improve bioavailability of peptide drug delivery - See, Hock Ming (2018)
Peptide and protein therapeutics in the biomedical application has been widely researched in the past decades, however, their usage is hampered by various systemic barriers which greatly reduce the bioavailability and drug efficacy. Oral delivery is most preferred due to its great patient compliance and noninvasiveness, though the occurrence of proteolytic degradation and the presence of gastrointestinal barriers lower the drug stability and absorption effectiveness of protein/peptide drugs. Direct structural modifications, carrier systems, absorption enhancers and enzyme inhibitors are being studied to overcome the stability and absorption issues. Among these delivery strategies, carrier systems provide lots of flexible possibilities and favorable advantages to facilitate oral delivery, while liposomes being the most potential candidate to address these oral delivery issues. For possible future developments to improve the liposomal carrier systems, vitamin B12 grafted liposomes and the coadministration of archaeal lipids modified liposomes with bile salts as absorption enhancers are also discussed.